2021
DOI: 10.3390/cancers13236009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Overall Survival between Surgical Resection and Radiofrequency Ablation for Hepatitis B-Related Hepatocellular Carcinoma

Abstract: It remains controversial whether surgical resection, compared to radiofrequency ablation (RFA), improves overall survival (OS) in patients with early hepatocellular carcinoma (HCC). This study aimed to compare OS after RFA with that after resection for HCC. This retrospective study included patients who underwent RFA or surgical resection as initial treatment for hepatitis B virus (HBV)-related HCC at a very early or early stage. A total of 761 patients (RFA, n = 194; resection, n = 567) from Seoul National Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…There have been some reports comparing the efficacy of RFA with SR by clinical data or database analysis. In one study, an MVI prediction model using multivariate logistic regression analysis indicated that SR had a lower rate of early recurrence than RFA ( P < 0.05) ( 18 ). Moreover, another study revealed that compared with RFA, LLR laparoscopic hepatectomy ensures a comparable better postoperative condition in elderly patients with solitary HCC (< 3 cm) located in the anterolateral segment despite longer hospital stay and operative time, considering overall survival rates, which was consistent with our results ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some reports comparing the efficacy of RFA with SR by clinical data or database analysis. In one study, an MVI prediction model using multivariate logistic regression analysis indicated that SR had a lower rate of early recurrence than RFA ( P < 0.05) ( 18 ). Moreover, another study revealed that compared with RFA, LLR laparoscopic hepatectomy ensures a comparable better postoperative condition in elderly patients with solitary HCC (< 3 cm) located in the anterolateral segment despite longer hospital stay and operative time, considering overall survival rates, which was consistent with our results ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of HCC increased after the age of 40 years, and it was estimated that the incidence of HCC will increase by approximately 59% by 2030, more than 50% of which will be in people aged 65 years or above ( 15 , 16 ). Compared with the younger population, complications such as diabetes, poor cardiopulmonary function, and renal insufficiency are common for elder adults (aged ≥65 years), which leading to higher severity and poorer prognosis after SR or RFA ( 11 , 17 , 18 ). Therefore, a more careful evaluation of the risk-benefit ratio in terms of SR and RFA treatment is required.…”
Section: Introductionmentioning
confidence: 99%
“…The liver plays a key role in the body’s detoxification and metabolism process. Liver cancer is formed by viruses and carcinogens that cause uncontrolled liver cells and pathological changes in the human body. Liver cancer is a serious threat to human health for a long time, and it is a malignant tumor with a high incidence and fatality rate. , At present, the main methods used to treat liver cancer are surgical resection, radiotherapy, and chemotherapy. , However, patients with advanced liver cancer are prone to face the problems of ineffective chemotherapy, drug resistance, and recurrence after surgical resection. , Eventually, patients may lose their confidence and motivation for treatment. , Therefore, designing a method for early detection and early treatment of liver cancer will bring powerful help to the rehabilitation of liver cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients submitted to MWA were, in fact, older, with slightly more compromised performance status, suffering more often from cirrhosis, more frequently affected by diabetes, and with slightly higher bilirubin and lower platelet count, similarly to other contemporary studies. [ 15 ] The researchers decided indeed to carry out a propensity score adjustment to restrict the analysis to a subgroup of comparable subjects, finally including less than half of the total surgical population. Probably, only a restricted population of patients is really identically suitable for both resection and ablation, and indeed a recently published randomized trial comparing surgery to ablation [ 14 ] had to be prematurely terminated because of insufficient recruitment of patients eligible for randomization.…”
mentioning
confidence: 99%
“…Ablation will likely remain offered as the reference technique to more‐fragile patients, in keeping with the multidisciplinary choices. [ 1,15 ] Why are then the present data [ 1 ] useful nonetheless? They reassure physicians that MWA, deployed by the most skilled operators, provide no worse of an outcome than resection, even for larger‐than‐usual single HCC; thus, we should not force indications for surgery, even laparoscopic, for patients not perfectly suitable for it.…”
mentioning
confidence: 99%